Nomogram to predict live birth in infertile women with adenomyosis undergoing IVF/ICSI treatment: a retrospective cohort study - Li, Zhongyuan; Chen, Wei; Sun, Xiaohan; Zhao, Xueqing; Hu, Jingmei; Ge, Li; Wang, Wenting; Zhang, Ping (Frontiers in Endocrinology, 2025)
PurposeThe study aimed to develop a nomogram to predict live birth outcomes in infertile women with adenomyosis undergoing IVF/ICSI treatment.Materials and methodsData were collected from the Center for Reproductive Medicine, Shandong University, between January 2016 and December 2020. This study included 222 fresh embryo transfer (ET) cycles and 266 frozen embryo transfer (FET) cycles. Patients were divided into a modeling cohort and a validation cohort. In the modeling cohort, multivariable logistic regression was used to generate the predictive model and construct the nomogram. The predictive model was subsequently validated and calibrated.ResultsIn total, 249 patients (51.0%) achieved clinical pregnancy, and 165 patients (33.8%) had a live birth. Predictive variables in the final model included mean initial uterine diameter, age, body mass index (BMI), type of infertility (primary or secondary), stage of transferred embryo, endometrial thickness, number of embryos transferred, and pregnancy type. The area under the receiver operating characteristic (ROC) curve for the final prediction model was 0.915 (95% confidence interval [CI]: 88.6%–94.3%) in the modeling cohort and 0.940 (95% CI: 90.3%–97.6%) in the validation cohort. Calibration curves and the Hosmer–Lemeshow (H–L) test demonstrated excellent consistency between predicted and actual live birth outcomes.ConclusionsThis study established a well-calibrated predictive model capable of accurately forecasting live birth outcomes in infertile women with adenomyosis undergoing IVF/ICSI treatment.